Investigation of Healthy Lifestyle Habits of Class Teacher Candidates in the Covid- 19 Period - Erdoğan, Ramazan; Aydemir, İsa; Yılmaz, Metin (My University, 2021)
This research was conducted to determine the healthy lifestyle habits of primary school teachercandidates during the covid-19 process. In the research 132 (99 Female, 33 Male) volunteerclassroom teacher candidates who were studying at Fırat University Faculty of Education andselected by random sampling method participated. \"Personal Information Form\" was applied todetermine the demographic information of the participants, and an online questionnaire form wasapplied to determine the nutritional habits and physical activity levels. Results; Differences wereobserved in the dietary habits and physical activity levels of the research group before and afterthe pandemic period. It has been determined that the pandemic period caused changes in the eatinghabits of the participants and that most of them changed in the number of meals, daily fluidconsumption and the foods they consumed during snacks. During the pandemic period, it was seenthat the majority of the research group did not do physical activity regularly and there was adecrease in physical activity, an increase in body weight and they did their physical activities athome. As a result, it was observed that the nutrition habits of class teacher candidates werenegatively affected and their physical activity levels decreased during the Covid-19 process. It isthought that informing individuals about healthy nutrition and physical activity will positivelyaffect their quality of life.
Keywords: Beslenme ve Diyetetik; Eğitim; Eğitim Araştırmaları